2016
DOI: 10.1080/01694243.2016.1199217
|View full text |Cite
|
Sign up to set email alerts
|

Effect of surface conditioning methods, adhesive systems and resin composite on repair strength of dimethacrylate and silorane resin composites

Abstract: (2016). Effect of surface conditioning methods, adhesive systems and resin composite on repair strength of dimethacrylate and silorane resin composites. Journal of Adhesion Science and Technology, 30(24)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 25 publications
0
3
0
Order By: Relevance
“…The sample size was determined by preliminary tests comparing with previous values published (Lima et al, 2016), in which that number of specimens yielded adequate power at α = 0.05, this sample size reached a power of 1 for detecting statistically significant differences. Data normality and homogeneity were verified by Kolmogorov-Smirnov and Levene tests, respectively.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The sample size was determined by preliminary tests comparing with previous values published (Lima et al, 2016), in which that number of specimens yielded adequate power at α = 0.05, this sample size reached a power of 1 for detecting statistically significant differences. Data normality and homogeneity were verified by Kolmogorov-Smirnov and Levene tests, respectively.…”
Section: Discussionmentioning
confidence: 99%
“…Success in repair procedures depends on obtaining an adequate adhesive interface between the aged and new resin composite. Several studies (Baur & Ilie, 2013;Lima et al, 2014;Baena et al, 2015;Ahmadizenouz et al, 2016;Lima et al, 2016;Fornazari et al, 2017) showed that the combination between the surface treatment to be repaired and the use of adhesive systems increase the bond strength between the composites. In this study, it was simulated restorations performed using a bulkfill resin composite and evaluated the bond strength of repairs performed with different adhesive systems and resin composites.…”
Section: Discussionmentioning
confidence: 99%
“…Silane is then applied to form a bond with the bonding agent 49 . Other studies 53‐57 showed that applying coupling agent followed by TSC improved bond strength of the ceramics. In our study, this technique failed to improve the microtensile bond strength to all CAD/CAM ceramic groups, consistent with others 58 .…”
Section: Discussionmentioning
confidence: 99%